Information System Design Activities Of Kuliah Kerja Nyata Using Single Linkage Method - Sugiarto -; Chrystia Aji Putra (Proceeding International Conference on Information Technology and Business, 2017)
The registration system of Kuliah Kerja Nyata (KKN) conducted at UPN